1992
DOI: 10.3354/meps088271
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of a small Antarctic diatom (Chaetoceros sp.) to simulated environmental constraints associated with sea-ice formation

Abstract: The physiological responses of a small unicellular Chaetoceros species, isolated from the Weddell Sea, Antarctica, to changes in temperature, salinity and irradiance simulating those that occur during new-ice formation were investigated. The combination of increased salinity, increased quantum irradiance and decreased temperature significantly reduced growth and photosynthetic rates compared to the control, although cellular metabolism was not inhibited. The cells retained the capacity to photoacclimate, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Two diatom species from sea ice have been shown to photosynthesize in culture at a temperature of-8°C and a salinity of 145 (Aletsee and Jahnke, 1992). Interestingly, several studies have suggested that algal tolerance to high salinities increases with lower temperatures (Aletsee and Jahnke, 1992;Gleitz and Thomas, 1992). The capacity of different phytoplankton species to acclimate to low temperatures and high salinities will determine their survival during ice formation, and subsequently which species are able to colonize the ice (Gleitz and Thomas, 1993;Grossmann and Gleitz, 1993).…”
Section: Sea Icementioning
confidence: 99%
“…Two diatom species from sea ice have been shown to photosynthesize in culture at a temperature of-8°C and a salinity of 145 (Aletsee and Jahnke, 1992). Interestingly, several studies have suggested that algal tolerance to high salinities increases with lower temperatures (Aletsee and Jahnke, 1992;Gleitz and Thomas, 1992). The capacity of different phytoplankton species to acclimate to low temperatures and high salinities will determine their survival during ice formation, and subsequently which species are able to colonize the ice (Gleitz and Thomas, 1993;Grossmann and Gleitz, 1993).…”
Section: Sea Icementioning
confidence: 99%
“…reduced temperature and light at increased salinities (Palmisano & Sullivan 1982, Aletsee & Jahnke 1992, Gleitz & Thomas 1992. However, productivity of sea ice algae during winter is greatly hindered by adverse environmental conditions, and daily nrnrllrrtinn ratnc arP i i~i i a l l y 1 tn 2 o r d e r s of m a~n i t u d e r * .…”
Section: Introductionmentioning
confidence: 99%
“…For example, these microalgae are exposed to a wide range of salinities during their growing season. As pelagic algae become incorporated into the growing sea‐ice lattice in winter, they are confined into microscopic channels and pockets within the ice that contain hypersaline brine (Gleitz and Thomas 1992). Brine channels provide a niche for sea‐ice algae where salinity can exceed 100‰ (Gleitz et al.…”
mentioning
confidence: 99%
“…There have been relatively few studies on the physiological impact on microalgae during sea‐ice formation, in comparison to the decay and melting of sea ice (Gleitz and Thomas 1992). During the process of ice formation, the salinity of the interstitial brine can increase to >60‰ (Vargo et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation